Perlindungan Hukum terhadap Penyandang Disabilitas Korban Kekerasan Seksual: Studi Putusan Nomor 78/PID.SUS/2024/PN RAH - Huring, Vinna Clarissa; Prasetyo, Boedi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Legal protection for victims resulting from a criminal act must be provided to every citizen, including people with disabilities. This study explains that the judge's decision is based on the facts revealed during the trial, with a specific example in the case of decision 78/PID.SUS/2024/PN RAH. This study uses a normative juridical legal approach. The approaches used in this study are the case approach, the statutory approach, and the conceptual approach. Decision Number 78/PID.SUS/2024/PN RAH substantively acknowledges the vulnerability of victims with disabilities by making powerlessness an aggravating factor and applying the criminal norms of Law No. 12/2022, thus emphasizing the perpetrator's responsibility. However, the decision does not outline crucial procedural accommodations such as legal and psychosocial assistance, disability-sensitive medical/forensic examinations, accessible communication, and examination room arrangements, resulting in a gap between legal recognition and the realization of the right to access justice and the practical recovery of victims. The imposition of fines has the dual potential of acting as both a retributive sanction and a restorative instrument if there is a clear allocation mechanism. However, because the decision does not regulate the management or restitution clause of the fine, the opportunity to fulfill distributive and restorative justice for the victim is missed. Therefore, the imposition of fines should ideally be accompanied by a restitution obligation, a transparent mechanism for fund management, and a guarantee of service referrals so that the financial sanction truly repairs the victim's losses, rather than simply punishing the perpetrator.